2016
DOI: 10.1002/lary.26333
|View full text |Cite
|
Sign up to set email alerts
|

Cellular source and proinflammatory roles of high-mobility group box 1 in surgically injured rat vocal folds

Abstract: Objectives High mobility group box 1 (HMGB1) is a chromatin-binding protein located in the cell nucleus. Following injury, immunocompetent cells secrete HMGB1 to the extracellular milieu under the stimulation of pro-inflammatory cytokines. Extracellular HMGB1 acts a “danger signal” that instigates the innate immunity and tissue repair. We previously reported HMGB1 in the vocal fold extracellular compartment between Day 3 and Day 7 following surgical injury. In this study, we further investigated the cell sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
(48 reference statements)
1
13
0
Order By: Relevance
“…Further, fibroblasts remain the dominant cell type at Day 1 (53.81%) and Day 2 (29.37%) despite the infiltration of neutrophils and macrophages into the acute wound environment. Previous work showed that both macrophages and fibroblasts were the major cell source of damage-associated molecular patterns (DAMP), namely high mobility group box-1, in modulating the inflammatory cytokine production in acute vocal fold injury [67,109]. Our data and others collectively suggest immunological and repair functions of fibroblasts that are unique in vocal fold microenvironment [110,111].…”
Section: Discussionsupporting
confidence: 69%
“…Further, fibroblasts remain the dominant cell type at Day 1 (53.81%) and Day 2 (29.37%) despite the infiltration of neutrophils and macrophages into the acute wound environment. Previous work showed that both macrophages and fibroblasts were the major cell source of damage-associated molecular patterns (DAMP), namely high mobility group box-1, in modulating the inflammatory cytokine production in acute vocal fold injury [67,109]. Our data and others collectively suggest immunological and repair functions of fibroblasts that are unique in vocal fold microenvironment [110,111].…”
Section: Discussionsupporting
confidence: 69%
“…Dysregulation of TNF-α has been associated with multiple physiological dysfunctions and diseases such as cancer 33 , Alzheimer's disease 34 , major depression 35 , and inflammatory bowel disease 36 . To demonstrate the potential clinical application of our platform, protein samples extracted from surgically injured rat vocal fold tissues 37 were subjected to both conventional and μPAD-based ELISAs for evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we conducted sandwich ELISA for detection of TNF-α in protein extractions from injured rat vocal folds 2 days ( n = 4) and 4 weeks ( n = 5) following surgery 37 . We also benchmarked our platform through testing the same samples using a commercial ELISA kit (ab100785, Abcam) on a 96-well plate.…”
Section: Resultsmentioning
confidence: 99%
“…Ongoing work on parallelizable calibration automation is being developed to refine the parameter values of the VF-ABM with additional vocal fold data collected in our laboratory (Li et al, 2012 ; Heris et al, 2015 ; Latifi et al, 2016 ; Li-Jessen et al, 2017 ) and others (King et al, 2015 ; Kishimoto et al, 2016 ). Those works are necessary to improve the biological representation of the VF-ABM for the ultimate clinical application.…”
Section: Discussionmentioning
confidence: 99%